The Effect of Financial Compensation for Farmland Acquisition on Household Welfare: The Yogyakarta International Airport Development Case - Yudha Purbawa (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Background Problems: Land acquisition is a major issue in development policy, and compensation is often described as being inadequate; meanwhile, adequate compensation is the key element of fairness. Main Objectives: The objective of this study is to examine the impact on household welfare of financial compensation for farmland acquisition for new airport development. Novelty: This study utilizes land acquisition for the new Yogyakarta International Airport (YIA) because this area provides a reasonable case for evaluation. Research Methods: A quasi-experimental design is used to draw a causal relationship. A questionnaire survey has been conducted with 452 households, consisting of 207 households in the treatment group and 245 households in the control group. Finding/Results: On average, the financial compensation for the farmland acquired for the new airport development increased a household’s total annual income by as much as 32.06%, especially the income that was generated from self-owned business and farmland activity, and it also increased their total annual expenditures by as much as 26.55%, especially those related to food, energy (LPG and fuel), vehicles, internet and phone, religion, social relationships, and insurance. Conclusion: This study highlights that financial compensation for farmland acquisition for tertiary industry, specifically a new airport development, has a positive impact on both the total annual income and the total annual expenditures.